Promethee-Based Prioritization of Energy-Saving Strategies in Public Office Buildings: An Energy Audit Approach - Galugu, Indrayati; Fahmi Misbahuddin, Afif (Energy Insights, 2026)
This study aims to find out how the level of electrical energy used in the North Kolaka Regency Food Crops and Horticulture Office building and analyze energy-saving opportunities that can be applied to the building.  This study uses a quantitative descriptive method.  The data collection techniques used are documentation, observation and measurement.  In this study, the researcher analyzed the data descriptively and provided an overview of the Energy Consumption Intensity of electricity using the Promethee Multi Criteria Decision Making (MCDM) method. The results of this study show that the total power installed in the North Kolaka Regency Food Crops and Horticulture Office building is 7.700 VA with an average Energy Consumption Intensity value of 1,994 kWh/m2 in the building. The load that uses the largest electrical energy in the building is 1 PK AC of 1,087.8 kWh. Based on the analysis of electrical energy saving opportunities at the Food Crops and Horticulture Office of North Kolaka Regency, three alternative savings efforts were obtained, namely no-cost, low cost and high cost opportunities. By using the Promethee Multi Criteria Decision Making (MCDM) Method, calculations were carried out to determine the energy-saving opportunities that were prioritized to be applied to the building and alternative results of low cost opportunities were obtained.